Kinetics of the reaction of hardening of copper minerals from complex sulfur of Marañon Complex - Lovera Dávila, Daniel (2010)
It has been obtained a good quality copper cement from copper-zinc sulphides ores of the east peruvian Andes at Marañon complex zone using integrated metallurgical processes, that makes easier the possibility to give technological value to peruvian concentrates of copper. Monitoring obtained products employing combined techniques such the X-Ray diffraction or the Mössbauer spectroscopy allow us to have a better information of the existing elements and help to control and optimize the metallurgical processes. With the Cementation Cinetic Equation there have been carried out simulations of the process, considering the process related variables, like time, agitation, solution concentration, pH, etc. Recovery has reported up to 70% of copper, that gives the way to improve national ore and concentrate extraction costs and open a great possibility to apply it to postergated small and medium mining project and operations, using LIX-SX-Cementation and/or LIX-Resins-Cementation intensive technologies.